2007
DOI: 10.17796/jcpd.31.4.d7p31201572n72h2
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Changes in Dental Arches After Treatment with a Prefabricated Functional Appliance

Abstract: The purpose of this study was to determine the effect of the T4K, a prefabricated functional appliance, on the transverse and anterior-height dimensions of the maxillary and mandibular dental arches. Dimensions before and after treatment were measured on the sample, then, natural growth was subtracted from the treatment effects and compared with twice the error of the method. A clinically significant increase of both dimensions was observed in the maxilla and mandible when Class II malocclusion patients were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 2 publications
3
30
0
2
Order By: Relevance
“…Those authors concluded that, in the context of a public healthcare setting, PFAs were preferred over activators due to their low cost and reduced chair time . Unfortunately, most other studies involving PFA's have not reported compliance data . One study reported a non‐compliance rate of 31% for Myobrace ® , which is comparable to that reported with a Twinblock appliance in another clinical trial .…”
Section: The Evidence Base Supporting Prefabricated Functional Appliamentioning
confidence: 96%
See 1 more Smart Citation
“…Those authors concluded that, in the context of a public healthcare setting, PFAs were preferred over activators due to their low cost and reduced chair time . Unfortunately, most other studies involving PFA's have not reported compliance data . One study reported a non‐compliance rate of 31% for Myobrace ® , which is comparable to that reported with a Twinblock appliance in another clinical trial .…”
Section: The Evidence Base Supporting Prefabricated Functional Appliamentioning
confidence: 96%
“…Other dental effects of PFAs include a reduction in overbite, improvement in lower incisor crowding and an improvement of Class II molars towards Class I . The transverse effects of PFAs are less commonly reported although they seem negligible since one study reports 1‐1.5 mm of arch expansion after 1 year of use …”
Section: The Evidence Base Supporting Prefabricated Functional Appliamentioning
confidence: 99%
“…With regard to dental arches, prefabricated functional appliances stimulate transverse development in patients with crowding, and their effects appear to be greatest at the bimolar width of the first premolars rather than the first permanent molars [22]. Concordantly, the 2 patients in this case exhibited increased width between their deciduous canines or first deciduous molars, rather than their first permanent molars.…”
Section: ⅲ Discussionmentioning
confidence: 71%
“…It thus appears that the prefabricated functional appliance stimulates further transverse development overlapping that produced by natural growth, which may be an asset when treating patients with crowding caused by decreased maxillary or mandibular transverse development [19]. Thus, it may be inferred that most of the effects seen were because of the use of the preorthodontic trainer.…”
Section: Discussionmentioning
confidence: 99%